Influence of SDHI Seed Treatment on the Physiological Conditions of Spring Barley Seedlings under Drought Stress - Dominika Radzikowska; Monika Grzanka; Przemysław Łukasz Kowalczewski; Romana Głowicka-Wołoszyn; Andrzej Blecharczyk; Marcin Nowicki; Zuzanna Sawinska (Agronomy, 2020)
Seed treatments help reduce the pathogen load and thus improve the condition of plants from their earliest developmental stages, but they can have impacts beyond their basic fungicide protection role. In this study, we investigated how seven spring barley seed treatments affected the plants’ physiological state. The tested seed treatments differed significantly in their impacts on the vigor parameters of barley seeds and on the physiological state of seedlings under drought stress and after regeneration. Seed treatments based on substances from the succinate-dehydrogenase-inhibitors (SDHI) group did not cause inhibition of seedling growth and also display by the highest vigor index values. Using the analysis of photosynthesis-related parameters, we showed that seed treatments from the SDHI group provided a superior tolerance of the imposed drought in spring barley than other treatments. In addition to protection against abiotic stress, SDHI treatments also rendered a higher efficiency of photochemical reactions in the treated plants.